SATU DASAWARSA BRICS: PELUANG DAN TANTANGAN: Narrative Literature Review - Muslimin Muslimin; Muji Rahmat Ramelan; Lis Andriani (Pustaka Peradaban, 2025)
This narrative literature review examines the opportunities and challenges faced by BRICS (Brazil, Russia, India, China, and South Africa) over the past decade, focusing on Indonesia's potential integration into the alliance. The study highlights key areas such as green growth, renewable energy adoption, economic integration, and geopolitical dynamics. BRICS countries have shown varying progress in transitioning to cleaner energy sources, with Brazil and China leading in renewable energy investments, while Indonesia faces challenges in reducing fossil fuel dependency. The review also explores the role of human capital, financial development, and intellectual property rights in driving sustainable growth. Despite internal disparities and geopolitical tensions, BRICS strengthens its influence in global economic governance. Indonesia's participation in BRICS offers strategic economic and geopolitical advantages, including diversification of trade partnerships and technology transfer, but requires careful management of risks such as fossil fuel dependency and geopolitical competition. The study concludes that BRICS must address internal challenges, including corruption and institutional weaknesses, to fully realize its potential as a global economic force. Tinjauan literatur naratif ini mengkaji peluang dan tantangan yang dihadapi oleh BRICS (Brasil, Rusia, India, China, dan Afrika Selatan) selama dekade terakhir, dengan fokus pada potensi integrasi Indonesia ke dalam aliansi tersebut. Studi ini menyoroti area-area kunci seperti pertumbuhan hijau, adopsi energi terbarukan, integrasi ekonomi, dan dinamika geopolitik. Negara-negara BRICS telah menunjukkan kemajuan yang bervariasi dalam transisi ke sumber energi yang lebih bersih, dengan Brasil dan China memimpin dalam investasi energi terbarukan, sementara Indonesia menghadapi tantangan dalam mengurangi ketergantungan pada bahan bakar fosil. Tinjauan ini juga mengeksplorasi peran modal manusia, pengembangan keuangan, dan hak kekayaan intelektual dalam mendorong pertumbuhan berkelanjutan. Meskipun terdapat disparitas internal dan ketegangan geopolitik, BRICS terus memperkuat pengaruhnya dalam tata kelola ekonomi global. Partisipasi Indonesia dalam BRICS menawarkan keuntungan ekonomi dan geopolitik strategis, termasuk diversifikasi kemitraan perdagangan dan transfer teknologi, tetapi memerlukan pengelolaan risiko yang cermat seperti ketergantungan pada bahan bakar fosil dan persaingan geopolitik. Studi ini menyimpulkan bahwa BRICS harus mengatasi tantangan internal, termasuk korupsi dan kelemahan institusional, untuk sepenuhnya mewujudkan potensinya sebagai kekuatan ekonomi global.